Strategic environmental assessment (SEA) of socio-economic systems: a systematic review - Tamošaitienė, Jolanta; Kapliński, Oleg (Technological and Economic Development of Economy, 2013)
Today, Strategic Environmental Assessment (SEA) of Socio-Economic Systems exists in micro, meso and macro environments. A complicated process is required to find a rational solution that would include a large number of problems and criteria. Therefore, existing MCDM methods must be used as well as new ones developed. Notwithstanding SEA of Analysis of Socio-Economic Processes, there is little research examining factors of use of MCDM methods; thus, a more in-depth analysis should be undertaken. This study applied a systematic search of literature. A total of 73 papers from the academic literature containing such terms as ‘Strategic Environmental Assessment (SEA)’, ‘Socio-Economic Processes (SEP)’, ‘Socio-Economic Systems (SES)’, ‘Social Systems (SS)’, ‘Economical Systems (ES)’, ‘Decision-Making (DM)’ and ‘Multi Criteria Decision-Making (MCDM)’ were identified and reviewed. As to the eligibility problem in Strategic Environmental Assessment (SEA), criteria included studies on both Social and Economic Systems & Processes that examined development and trends related to SEA of Socio-Economic Processes. MCDM methods, assessment processes, data extraction and analysis were completed in all relevant studies. General activity fields in Strategic Environmental Assessment (SEA) of Socio-Economic Systems were analysed. The key issues of SEA in micro, meso and macro environment, Socio-Economic Systems and Socio-Economic Processes factors were prominent across all researched categories. As far as the analysis of Socio-Economic Systems & Processes, decision makers should be aware of the problem in its complexity and undertake multi-stage decision-making. To honour the contribution made by Prof Valentinas Podvezko contribution in the field of Decision-Making (DM) to Strategic Environmental Assessment (SEA) of Socio-Economic Systems using MCDM methods, and to commemorate his 70th anniversary, this article also highlights his academic career and research.